Parental child abduction across borders : an analysis of the international, Islamic and Malaysian legal framework - Sultan, Naheed (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2021)
Globalisation has given rise to diversity in many facets of life, including cross-cultural marriages. As much it sounds appealing, there are many implications and negative consequences of these types of marriages. One of which is Parental Child Abduction. It usually takes place when the marital relationship does not sustain and results in divorce. Apart from deciding who will get what and how much, in terms of wealth, one crucial decision is the custody of children. In many instances, parents do not want to take laws into their own hands, therefore, abduct their own children. Parental Child Abduction has become a global phenomenon now. Parental Child Abduction is not new to Malaysia as it has gained importance after the highly publicised case of Raja Bahrin. By looking at all these challenges, the international community unanimously approved, adopted, and signed the Hague Convention on Civil Aspects of International Child Abduction, 1980. The 1980 Child Abduction Convention is an attempt to address the problem by using an automatic return mechanism of the abducted child to his country of habitual residence and for the courts of that State to adjudicate on the issue of custody, but due to conflicting substantive and procedural laws in various countries, it is difficult to resolve the issue. This Convention works in countries who are a member to it and like many other Muslim countries, Malaysia is also not a member to it. The present research examined and made a thorough analysis of the dual legal system of Malaysia, namely both the civil law and Islamic law to know whether Malaysia has adequate legal and procedural laws to address the inevitable issues and implications of Parental Child Abduction within and across the border of Malaysia. The crux of the thesis lies in The Hague Abduction Convention on Civil Aspects of International Child Abduction,1980, which is critically explained with its compatibility with Islamic law. This is followed by proposing substantive reforms to cope with domestic and cross border Parental Child Abduction in Malaysia. Data were collected from one hundred and fifty (150) legislators and related authorities of various NGOs on issues related to Parental Child Abduction. The collected data was then analysed by using qualitative and quantitative legal research methods. The findings of this research reveal that there are legitimate concerns on the part of stakeholders and on the fact that the opinion on the ground is against the accession. The findings of the present research proposed to strengthen section 52 of the Child Act, to amend section 361 of the Penal Code, to employ more Sulh officers, to establish an Arbitration Tribunal or tahkim and to establish a mediation centre. These findings will have invaluable implications for policymakers and related stakeholders.